The Covenant - Lewis, Beverly; Nang ChanYeema (Minneapolis, MN USA Bethany House Publishers, 2002)
Amish traditions as seen through the eyes of Leah and Sadie Ebersol two courting-age sisters.
Keywords: Adult Fiction